BATAS ETIS INTERAKSI GURU-SISWA DIGITAL: ANALISIS KODE ETIK PERMENDIKBUDRISTEK 67/2024 DAN FATWA MUI 24/2017 - Slamet Faturrohman; Niki Amanatul Utami; Waqiatus Salamah; Ma’mun Hanif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The expansion of digital technology has significantly reshaped communication practices within educational settings, enabling teachers and students to interact through various digital platforms, including WhatsApp, Instagram, and other social media applications. While these platforms facilitate learning and information exchange, they also create new ethical challenges. During 2024–2025, several incidents involving inappropriate teacher-student digital interactions attracted public attention, ranging from excessive personal communication and inappropriate online comments to behaviors that blurred professional boundaries. Such phenomena underline the need for clearer ethical standards governing digital communication in education. This study aims to examine the ethical boundaries of teacher-student interactions in digital environments through the perspective of the Minister of Education, Culture, Research, and Technology Regulation Number 67 of 2024 and the Indonesian Ulema Council Fatwa Number 24 of 2017. Employing a qualitative library research design with a normative legal approach, this study analyzes regulatory documents, fatwas, and relevant scholarly literature using content analysis techniques. The findings indicate four essential ethical principles that should guide digital interactions between teachers and students: maintaining professional communication boundaries, protecting student privacy and personal data, promoting respectful and educational communication, and ensuring that digital engagement remains aligned with educational objectives and character formation. These findings suggest that the integration of legal regulations and religious ethical values can provide a comprehensive framework for strengthening teacher professionalism and safeguarding students in digital learning environments. Accordingly, schools are encouraged to formulate practical digital communication guidelines to support ethical and responsible educational interactions.